Effects of Lactobacillus combined with semidry flour milling on the quality and flavor of fermented rice noodles. (December 2019) - Geng, Dong-Hui; Liang, Tingting; Yang, Mei; Wang, Lili; Zhou, Xianrong; Sun, Xiaobin; Liu, Lu; Zhou, Sumei; Tong, Li-Tao
Abstract: To shorten the fermentation time and reduce the contamination with heterozygous bacteria during the process of fermenting rice noodles, pure bacterial fermentation combined with semidry flour milling was used to produce fermented rice noodles. The changes in the pH value and microbial community diversity of the rice slurries, the physicochemical properties of the rice flours, and the texture, cooking qualities, sensory qualities and volatile components of the rice noodles prepared with different fermentative methods were investigated. The results showed that the pure bacterial fermentation required 18 h to reach a stable pH value, while the natural fermentation required 54 h. In addition, compared with naturally fermented rice slurry, the bacterial community diversity of the pure bacterial fermented rice slurry was significantly lower, while the fungal community diversity did not differ significantly. Significant differences were observed in the content of the damaged starch, amylose and protein between semidry milled pure bacterial fermented (SP) and wet milled naturally fermented (WN) rice flours ( P  < .05), while these differences had no significant effect on the texture and cooking qualities of the SP and WN rice noodles ( P  > .05). In addition, the types of volatile components of the SP noodles were significantly lower than those of other noodles, while the primary volatile component categories of the SP noodles were consistent with that of the WN noodles, and they had a similar flavoring substance. Graphical abstract: Unlabelled Image Highlights: Pure bacterial fermentation and semidry milling were used to produce rice noodles. Semidry milled pure bacterial fermentation shortened the fermentation time. Lactobacillus significantly inhibited the growth of contaminant microorganisms. Pure bacterial fermentation improved the quality and flavor of rice noodles.